Development Of A Participatory Smart Madrasah Leadership Model Based On Socio-Cultural Values In The Society 5.0 Era - Masudi Masudi; Novi Darmayanti; Ah. Zakki Fuad (Universitas Pakuan, 2026)
This study aims to develop a participatory Smart Madrasah leadership model grounded in the social culture of the community in the Society 5.0 era at MA Darul Huda Gumukmas Jember. The research is driven by the growing demand for digital transformation in Islamic education, which requires leadership that not only adopts digital technology but also integrates local socio-cultural values and promotes stakeholder participation in educational governance. A qualitative field research approach was employed to explore leadership practices, social interactions, and the implementation of Smart Madrasah within a religious community context. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings reveal that Smart Madrasah development is supported by participatory leadership involving teachers, students, parents, alumni, religious leaders, and the wider community in collaborative decision-making. Values of mutual cooperation, deliberation, social solidarity, and Islamic ethics provide the cultural foundation for sustainable digital transformation. Furthermore, technology integration is implemented through strengthening digital literacy, fostering dialogic communication, and reinforcing Islamic character education. This study contributes to Islamic educational leadership theory by proposing a culturally responsive participatory leadership model that supports sustainable Smart Madrasah development in the Society 5.0 era.